2023
DOI: 10.3390/molecules28031227
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Transformation Products Formed by Ozonation—Does Degradation Occur?

Abstract: The efficiency of an advanced oxidation process (AOP) using direct and indirect ozonation for the removal of pharmaceutical residues from deliberately spiked deionized water was examined. Both direct and indirect ozonation demonstrated 34% to 100% removal of the parent compounds. However, based on the products’ chemical structure and toxicity, we suggest that despite using accepted and affordable ozone and radical concentrations, the six parent compounds were not fully degraded, but merely transformed into 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Levofloxacin is considered the primary antimicrobial agent that causes clinical problems with ARB [97]. Previous studies have reported that ozone and/or UV treatment reduces ecotoxicological effects to approximately 1/10-1/20,000 compared to untreated compounds [47,[98][99][100]. On the other hand, some researchers pointed out that the toxicity increases approximately 2-100 fold in some cases [99,100].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Levofloxacin is considered the primary antimicrobial agent that causes clinical problems with ARB [97]. Previous studies have reported that ozone and/or UV treatment reduces ecotoxicological effects to approximately 1/10-1/20,000 compared to untreated compounds [47,[98][99][100]. On the other hand, some researchers pointed out that the toxicity increases approximately 2-100 fold in some cases [99,100].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that ozone and/or UV treatment reduces ecotoxicological effects to approximately 1/10-1/20,000 compared to untreated compounds [47,[98][99][100]. On the other hand, some researchers pointed out that the toxicity increases approximately 2-100 fold in some cases [99,100]. It is known that differences in susceptibility to these toxic effects occur in different target species, and that under conditions where multiple compounds coexist, weakening or strengthening effects would occur compared to exposure to a single substance [101,102].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the advanced oxidation process, indirect ozonation, according to the information gathered, is inefficient for removing persistent pollutants (e.g., some emerging pollutants) [63].…”
Section: Indirect Ozonationmentioning
confidence: 99%
“…Its advantage is its swift reactivity with organic compounds, which does not require selection. It readily reacts with organic compounds at various positions in the gas phase, producing easily oxidizable intermediates [80].…”
Section: Copper-based Catalyst For Water Treatmentmentioning
confidence: 99%